PENGARUH PROFITABILITAS, KOMITE AUDIT DAN DIVERSIFIKASI GENDER TERHADAP PENGUNGKAPAN INFORMASI LINGKUNGAN - Lindrawati, Lindrawati; Trimuryanti, Maria Cyntia (Jurnal Kajian Akuntansi dan Auditing, 2025)
The development of the industrial sector which is increasingly complex makes many companies ignore environmental aspects in running their business. Environmental problems caused by improper management of company activities cause various environmental damages. This has made companies start thinking about paying attention to the environment and presenting this information in annual reports. This study aims to analyze the impact of profitability, audit committee, and gender diversification on environmental information disclosure. The research design is a quantitative research. The data type used is quantitative and qualitative in the form of annual reports and sustainability reports. The research objects are mining and manufacturing companies listed on the IDX and participating in PROPER. Data analysis used multiple regression analysis. The research results that the audit committee had a positive effect on disclosing environmental information, shows that the more audit committee members are able to pressure management to increase disclosure of the company's environmental information. Profitability and gender diversification had no effect on disclosing environmental information.